Chloropicrin Fumigant REDs Regulations Overview - Andrew MacRae; Joseph Noling (EDIS, 2010)
HS1168, a 10-page fact sheet by Andrew MacRae and Joseph Noling, provides an overview of the new measures that will be required for fumigant applicators and growers using chloropicrin. Published by the UF Department of Horticultural Sciences, April 2010.